Retrospective, multi-centre, open-label study on the use of alemtuzumab for relapsing–remitting multiple sclerosis in clinical practice: A 4-year follow-up - A. Pato-Pato; P. Gabeiras-Araujo; M. Lorenzo-García; C. Hernandez-Cerón; J.R. Lorenzo-González; D.A. García-Estévez (Neurology Perspectives)
Introduction: The efficacy and safety of alemtuzumab for patients with relapsing–remitting multiple sclerosis (RRMS) have been demonstrated in clinical trials. However, due to the limitations of these studies, it is important to assess the effects of the drug in clinical practice. The purpose of this study is to describe the effectiveness of alemtuzumab in terms of the number of relapses per year in patients with RRMS in the clinical setting. As secondary objectives, we evaluated its impact on disability and neuroimaging findings, as well as its tolerability and safety following administration. Methods: We conducted a retrospective, multi-centre, open-label study by reviewing the clinical records of patients receiving alemtuzumab for RRMS treatment. Results: A total of 32 patients were included at the beginning of the 4-year follow-up period. The mean number of relapses per year remained below 0.35 during follow-up, compared to 1.25 per year before treatment. Disability, as measured with the Expanded Disability Status Scale, improved during the first 2 years, and remained stable thereafter. Neuroimaging revealed a decrease in disease activity. The most frequent adverse effects were infusion-related reactions and infections. Conclusions: Alemtuzumab has been shown to be effective in clinical practice in reducing the number of relapses per year, improving disability and decreasing disease activity on brain MRI in patients with MS, with adequate tolerability and safety. However, prevention and monitoring strategies continue to be necessary. Resumen: Introducción: La eficacia y seguridad de Alemtuzumab en pacientes con esclerosis múltiple remitente-recurrente (EMRR) ha sido demostrada en ensayos clínicos. Sin embargo, por las limitaciones de éstos, es importante comprobar cómo se comporta en condiciones de práctica clínica habitual. Nuestro objetivo es describir la efectividad de alemtuzumab medida en número de brotes anuales en práctica clínica en pacientes con EMRR. Como objetivos secundarios valoramos la efectividad en estado de discapacidad y pruebas de neuroimagen, así como la tolerabilidad y seguridad tras su administración. Método: Hemos realizado un estudio abierto retrospectivo multicéntrico para el cual se han revisado las historias clínicas de pacientes que han recibido tratamiento con alemtuzumab por EMRR. Resultados: Se incluyeron un total de 32 pacientes al comienzo de los 4 años de seguimiento. La media de brotes anuales se mantuvo por debajo de 0.35 frente a los 1.25 brotes por año antes del tratamiento. La discapacidad medida por la escala EDSS mejoró durante el primer y segundo año, manteniéndose estable posteriormente. Se observó un descenso en la actividad de la enfermedad por pruebas de neuroimagen. Los efectos adversos más frecuentes fueron las reacciones de perfusión y las infecciones. Conclusiones: Alemtuzumab ha demostrado ser efectivo en práctica clínica en pacientes con esclerosis múltiple en la reducción del número de brotes anuales, la mejora del grado de discapacidad, y la disminución de la actividad en resonancia magnética craneal, con un adecuado perfil de tolerabilidad y seguridad, necesitando medidas de prevención y control.